2018
DOI: 10.1038/s41598-018-29528-x
|View full text |Cite
|
Sign up to set email alerts
|

MPP+ decreases store-operated calcium entry and TRPC1 expression in Mesenchymal Stem Cell derived dopaminergic neurons

Abstract: Parkinson’s disease is a neurodegenerative disorder involving the progressive loss of dopaminergic neurons (DNs), with currently available therapeutics, such as L-Dopa, only able to relieve some symptoms. Stem cell replacement is an attractive therapeutic option for PD patients, and DNs derived by differentiating patient specific stem cells under defined in-vitro conditions may present a viable opportunity to replace dying neurons. We adopted a previously published approach to differentiate Mesenchymal Stem Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 65 publications
(68 reference statements)
0
13
0
Order By: Relevance
“…As L-type calcium channel blockers like isradipine have already gone into clinical trials for PD, TRPC1 performing the same physiological function in dopaminergic neurons could be looked at as a molecular target in PD (Simuni et al, 2010;Sun et al, 2017). Consistent with these results are the findings of Sun et al (2018a), where MPP + was found to reduce TRPC1 expression and storeoperated calcium entry in the mesenchymal stem cell-derived dopaminergic neurons.…”
Section: Trpc Involvement In Pdmentioning
confidence: 60%
“…As L-type calcium channel blockers like isradipine have already gone into clinical trials for PD, TRPC1 performing the same physiological function in dopaminergic neurons could be looked at as a molecular target in PD (Simuni et al, 2010;Sun et al, 2017). Consistent with these results are the findings of Sun et al (2018a), where MPP + was found to reduce TRPC1 expression and storeoperated calcium entry in the mesenchymal stem cell-derived dopaminergic neurons.…”
Section: Trpc Involvement In Pdmentioning
confidence: 60%
“…A previous study demonstrated the presence of stretch-activated calcium channels, which are required for mechanotransduction of MSCs, and voltage-gated calcium channels that are activated by membrane depolarization and mediate Ca 2+ influx [19]. Activation of A transient receptor potential canonical channel 1, which forms nonselective cation channels, is generally linked to stimulation of plasma membrane receptors coupled to PLC γ [20] and has been reported in dopaminergic differentiated MSCs [21]. Although the expression and functional statuses of this channel in multipotent MSCs are unknown, it is a possible component of SOCE mechanisms upon depletion of intracellular Ca 2+ stores.…”
Section: Discussionmentioning
confidence: 99%
“…That process protects DNs against the Cav1.3-mediated cell death. Neurotoxins that mimic PD symptoms, such as 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP), increase the activity of the Cav1.3 channel by downregulating the expression of TRPC1, which lead to a decrease in SOCE and the release of Ca 2+ from ER to the cytosol in DNs and mesenchymal stem cells ( Sun et al, 2018 ). It has been described that MPP + (1-methyl-4-phenylpyridinium), a toxic metabolite product of enzymatic activity of MAO-B on MPTP, kills DNs in SN ( Choi et al, 2015 ).…”
Section: Trps In Parkinson’s Diseasementioning
confidence: 99%